Anxiety, depression and cerebrovascular disease - Lučev, Emil; Tadinac, Meri; Lučev, Ivana Lučev, Josip (2006)
Background: Depression and anxiety as the risk factors significantly influence the development of ischemic stroke. On the other side, the disturbances in intracranial circulation affect the development of anxious and depressive disorders. Aim: To explore whether the patients with cerebrovascular disease, who have suffered ischemic stroke differ from those who have not, in depression and anxiety levels, as well as in the parameters of everyday functioning. Patients from all three groups were involved in adequate programs of pharmaceutical and physical therapy. Methods: There were four groups of participants (N=179) involved in the study: 1. healthy, 2. patients with cerebrovascular disease, 3. patients who suffered an ischemic stroke and did not receive psychotherapy and 4. patients who suffered an ischemic stroke and received psychotherapy. Zung SDS depression scale, Zung SAS anxiety scale, Mini mental state test MMSE and Granger adapted Barthel index were used in the study. All testings and therapies were conducted in the same microclimate conditions between 8 and 11 AM (1.1.2003-6.30.2005). Each patient was tested twice, 3 and 12 months after diagnosis. Results: One-way analysis of variance showed the statistically significant differences in levels of depression and anxiety between four groups included in the study 3 and 12 months after diagnosis. Conclusion: Participants with cerebrovascular disorders showed significantly higher levels of depression and anxiety than healthy participants. Patients who suffered an ischemic stroke and did not receive psychotherapy (group 3) had significantly higher levels of depression and anxiety than those who received psychotherapy (group 4).
Projekt MZOS
ENG